2016
DOI: 10.3758/s13428-016-0777-2
|View full text |Cite
|
Sign up to set email alerts
|

Spanish semantic feature production norms for 400 concrete concepts

Abstract: Semantic feature production norms provide many quantitative measures of different feature and concept variables that are necessary to solve some debates surrounding the nature of the organization, both normal and pathological, of semantic memory. Despite the current existence of norms for different languages, there are still no published norms in Spanish. This article presents a new set of norms collected from 810 participants for 400 living and nonliving concepts among Spanish speakers. These norms consist of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 52 publications
0
23
0
20
Order By: Relevance
“…More interesting, the present study found few linguistic as well as cultural differences worth mentioning. For instance, one of these differences in our study is evident in the concept "pavo" (turkey) from the Spanish norm (Vivas et al, 2017) that coincides in its higher value with the concept "peacock" from the English norm (McRae et al, 2005). The first cultural difference is evidenced by the fact that "turkey" is a typical everyday food in the United States, and a traditional Thanksgiving and Christmas dish.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…More interesting, the present study found few linguistic as well as cultural differences worth mentioning. For instance, one of these differences in our study is evident in the concept "pavo" (turkey) from the Spanish norm (Vivas et al, 2017) that coincides in its higher value with the concept "peacock" from the English norm (McRae et al, 2005). The first cultural difference is evidenced by the fact that "turkey" is a typical everyday food in the United States, and a traditional Thanksgiving and Christmas dish.…”
Section: Discussionmentioning
confidence: 63%
“…The semantic production norms in English (McRae et al, 2005) and Spanish (Vivas et al, 2017) were elaborated on a basis of 540 and 400 concrete concepts, respectively, using an intersection between both norms of 219 concepts. For the generation of verbal descriptors and the verbal semantic field for the 219 concepts, the production frequency of features for each concept was considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations